Power quality improvements in power factor correction Luo converter fed brushless direct current motor drive. (6th February 2014) - Singh, Bhim; Bist, Vashist
Summary This paper presents a power factor correction (PFC) Luo converter based voltage source inverter (VSI) fed brushless direct current (BLDC) motor drive using a single voltage sensor. A single‐phase diode bridge rectifier followed by a Luo converter operating in discontinuous inductor current mode (DICM) is used for the direct current link voltage control and PFC operation at alternating current (AC) mains. The speed control is achieved by varying the direct current link voltage of VSI and electronically commutating the BLDC motor using fundamental frequency switching of VSI for reduced switching losses. The proposed PFC‐based Luo converter fed BLDC motor drive is designed, and its performance is simulated and validated experimentally for achieving a unity power factor at AC mains over a wide range of speed control at universal AC mains. The achieved power quality indices are observed under the acceptable limits of international power quality standard such as IEC 61000‐3‐2. Copyright © 2014 John Wiley & Sons, Ltd.